THE USE OF DIFFERENTIATED EDUCATION IN HISTORY LESSONS: THEORY AND PRACTICE - Feruza Shakirovna Ilmurodova (European Science Publishing, 2024)
This article covers theoretical and practical aspects of the use of differentiated education in history lessons. In particular, in the process of teaching history, the processes of individual approach to low, gifted students are described, the assimilation of effective aspects of differential technology.
Keywords: student, history, Control, intellectual, interest, differential, acquisition, skills, psychology, pedagogy, theory, test, purpose.